Microstructure and mechanical properties of Al-TiCN composites prepared by spark plasma sintering. (13th November 2019) - Zeng, Wen; Yu, Daliang; Ma, Yilong; Qiu, Risheng; Cao, Xianlong; Deng, Hongda; Li, Chunhong; Shao, Bin; Guo, Donglin; Lan, Wei
Abstract: Al-TiCN composites were fabricated by spark plasma sintering (SPS). The effect of TiCN content (0, 1, 3, 5, 7 and 10 wt%) on the microstructure and mechanical properties of as-SPSed composites were investigated. Results show that TiCN particles are uniformly dispersed in Al powder except Al-10 wt% TiCN composite, which contains excessive TiCN particles results in agglomeration of TiCN particles. Besides, the hardness of composites increases with increasing TiCN content. The maximum hardness of composites is 35.2 HV, which is 14% higher than that of the Al matrix. Moreover, Al-7 wt% TiCN composite exhibits the most excellent comprehensive properties with its compressive strength at 45% strain higher by 11% as compared to the Al matrix. The superior mechanical properties of Al-TiCN composites were mainly attributed to Orowan strengthening due to TiCN particles.